Autologous haematopoietic stem cell transplantation versus low‐dose immunosuppression in secondary–progressive multiple sclerosis. (28th February 2022) - Mariottini, Alice; Bulgarini, Giovanni; Forci, Benedetta; Innocenti, Chiara; Mealli, Fabrizia; Mattei, Alessandra; Ceccarelli, Chiara; Repice, Anna Maria; Barilaro, Alessandro; Mechi, Claudia; Saccardi, Riccardo; Massacesi, Luca
Abstract: Background and purpose: Effectiveness of autologous haematopoietic stem cell transplantation (AHSCT) in relapsing–remitting multiple sclerosis (MS) is well known, but in secondary–progressive (SP)‐MS it is still controversial. Therefore, AHSCT activity was evaluated in SP‐MS using low‐dose immunosuppression with cyclophosphamide (Cy) as a comparative treatment. Methods: In this retrospective monocentric 1:2 matched study, SP‐MS patients were treated with intermediate‐intensity AHSCT (cases) or intravenous pulses of Cy (controls) at a single academic centre in Florence. Controls were selected according to baseline characteristics adopting cardinality matching after trimming on the estimated propensity score. Kaplan–Meier and Cox analyses were used to estimate survival free from relapses (R‐FS), survival free from disability progression (P‐FS), and no evidence of disease activity 2 (NEDA‐2). Results: A total of 93 SP‐MS patients were included: 31 AHSCT, 62 Cy. Mean follow‐up was 99 months in the AHSCT group and 91 months in the Cy group. R‐FS was higher in AHSCT compared to Cy patients: at Year 5, 100% versus 52%, respectively ( p  < 0.0001). P‐FS did not differ between the groups (at Year 5: 70% in AHSCT and 81% in Cy, p  = 0.572), nor did NEDA‐2 ( p  = 0.379). A sensitivity analysis including only the 31 "best‐matched" controls confirmed these results. Three neoplasms (2 Cy, 1 AHSCT) and two fatalities (2 Cy) occurred. Conclusions: This study provides Class III evidence, in SP‐MS, on the superior effectiveness of AHSCT compared to Cy on relapse activity, without differences on disability accrual. Although the suppression of relapses was observed in the AHSCT group only, AHSCT did not show advantages over Cy on disability, suggesting that in SP‐MS disability progression becomes based more on noninflammatory neurodegeneration than on inflammation. Abstract : Thirty‐one secondary–progressive multiple sclerosis (SP‐MS) patients treated with autologous haematopoietic stem‐cell transplantation (AHSCT) were matched 1:2 with cyclophosphamide (Cy)‐treated SP‐MS patients; outcomes were evaluated over long‐term follow‐up (mean = 96 months). AHSCT was superior to Cy in suppressing relapse activity, without differences in Expanded Disability Status Scale worsening, suggesting that in SP‐MS disability accrual becomes more based on noninflammatory neurodegeneration than on inflammation. A hint of superior efficacy of AHSCT was observed on progression‐free survival, suggesting a potential benefit of transplant in selected cases, and supporting the feasibility of randomized clinical trials comparing AHSCT with available treatments to provide conclusive evidence on this issue.